THE IRONY IN POETRY OF IBN MUNAIR AL-TARABULSI (DIED 548 H.) AND DUALISM OF SERIOUSNESS AND HUMOR - Dr. Mohammed Noori Abbass Khalef (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The cultural development that included life in the Abbasid Age, and what followed it of luxury and welfare cast its shadows on the poets, and its impact was prominent particularly on the proficient poets, and among results of this proficiency: the creativity and creating in the poetic purposes and arts. On the other hand, it showed the truth of the competition among them and conflicting in fawning to those of power and sultan, and this matter entirely applies on our poet Ibn Munair Al-Tarabulsi who showed to us the irony as a one of the arts that his poetic collection included. We embarked in searching about this ironical art in his poetry, and divided our research paper into three themes, which are: First: The irony and the humorous personality. Second: The Social and critical irony. Third: The political irony. Among results of this paper was that our poet had been mastered in using the irony as an arm of two blades, since he used it once upon time for entertainment, fun and joking as well as for criticism and reform in another, and for discretion, revenge and retaliation for times.